OBSERVATION OF WATER FLOW IN THE BALL VALVE BEFORE AND AFTER REPAIRS USING LAPPING MACHINES - David Tua Armando; Kusdi Prijono (Adisam Publisher, 2025)
In industrial piping systems, particularly in the oil and gas, petrochemical, and power generation sectors, ball valves are one of the most important components in controlling fluid flow. Defects on the contact surfaces pose risks of leakage, pressure drop, and flow disruption. These issues not only reduce system efficiency but also increase the potential for further damage. One of the commonly used repair methods is lapping, which is the process of smoothing the surfaces of the ball and seat to improve contact compatibility. The effectiveness of lapping is typically tested through a hydro test, where pressure stability over time serves as the primary indicator of post-repair flow performance. The primary objective of this study is to identify changes in pressure patterns and analyze trends in pressure stability in ball valves before and after repair using a lapping machine, evaluated through a hydro test. The research method is a quantitative experiment. Data collection is based on pressure-versus-time graphs from the hydro test on each ball valve in two conditions: before and after lapping. The results of the study show that before lapping, all ball valves experienced significant pressure fluctuations and were unable to maintain test pressure, indicating leakage. However, after the lapping process, the ball valves consistently showed a drastic improvement in performance, with stable pressure graphs and the ability to maintain maximum pressure (±900 - 920 psi) during the holding phase. These findings significantly contribute to the understanding that lapping is a highly effective repair method for restoring the sealing integrity of ball valves. The lapping process successfully restores the ball valve's ability to withstand pressure optimally, thereby improving water flow stability. Implicitly, this method can serve as an efficient practical solution for ball valve maintenance in industry.